The efficiency of liposomal paclitaxel versus docetaxel in neoadjuvant chemotherapy with the TPF regimen for locally advanced nasopharyngeal carcinoma: a retrospective study - Yang, Zhi; Zuo, Quan; Liu, Rong; Wu, Hui; Chen, Jia; Xiong, Li (Frontiers in Oncology, 2024)
PurposeThis retrospective study aimed to explore the efficiency and untoward reaction of liposomal paclitaxel versus docetaxel for locally advanced nasopharyngeal carcinoma (NPC).MethodsThis retrospective study included 115 patients diagnosed with NPC at our hospital between January 2018 and December 2021. Patients were stratified into two groups based on their treatment with either liposomal paclitaxel (n = 71) or docetaxel (n = 44) as part of the neoadjuvant chemotherapy regimen. Objective response rate (ORR), progression-free survival (PFS), locoregional relapse-free survival (LRFS), distant metastasis-free survival (DMFS), and overall survival (OS) were compared between the two groups.ResultsORR was significantly improved in the liposomal paclitaxel group than in the docetaxel group (62.0% versus 40.9%, p = 0.028). The 3-year PFS (PFS: 84.4% versus 77.5%, p = 0.303), LRFS (95.8% versus 94.4%, p = 0.810), DMFS (87.2% versus 83.0%, p = 0.443), and OS (90.7% versus 88.8%, p = 0.306) revealed no significance. The neutrophil-to-lymphocyte ratio [hazard ratio (HR): 3.510; p = 0.039] and distant metastasis (HR: 4.384; p = 0.035) were regarded as the risk factors using multivariate regression analysis. Moreover, the incidence of leukopenia at grades 1–2 in the liposomal paclitaxel group was significantly lower than that in the docetaxel group (28.1% versus 79.5%, p < 0.05).ConclusionsLiposomal paclitaxel had better efficacy in terms of short-term effects and lower incidence of leukopenia at grades 1–2 compared with the docetaxel group.